Addition of glycomacropeptide as fat replacer in sugar‐reduced Greek‐style yoghurt. (28th May 2020) - Godoy‐García, Liliana; Abadía‐García, Lucía; Cruz‐Aldaco, Karina; Castaño‐Tostado, Eduardo; Murúa‐Pagola, Beneranda; Amaya‐Llano, Silvia L
Abstract : The status of Greek‐style yoghurt (GSY) as a healthy food could be challenged by its inherent high fat content. Glycomacropeptide (GMP) possesses characteristics that make it suitable as a fat replacer. GMP powder was incorporated into fat‐reduced formulations of GSY. The addition of 0.75% GMP reduced the granular consistency and the syneresis of GSY by 50 and 10%, respectively, at all levels of fat evaluated. Flow curves and firmness analysis showed that adding GMP decreased the elastic and viscous modulus, and yoghurt firmness. The consumer acceptance of low‐fat GSY containing 0.75% GMP decreased only after 30 days of storage.